Oxidative environment and redox homeostasis in plants: dissecting out significant contribution of major cellular organelles - Das, Priyanka; Nutan, Kamlesh K.; Singla-Pareek, Sneh L.; Pareek, Ashwani (Frontiers in Environmental Science, 2015)
Plant cells are often exposed to oxidative cellular environments which result in the generation of toxic reactive oxygen species (ROS). In order to detoxify the harmful ROS, plants have evolved various strategies including their scavenging and antioxidant machinery. Plant cells contain many enzymatic and non-enzymatic antioxidants which aid in removing the toxic oxygen molecules. Various antioxidant molecules localized within different cellular compartments play crucial role(s) during this process, which includes both redox-signalling and redox-homeostasis. The present review gives an overview of cellular oxidative environment, redox signalling operative within a cell and contributions of major cellular organelles towards maintaining the redox homeostasis. Additionally, the importance of various antioxidant enzymes working in an orchestrated and coordinated manner within a cell, to protect it from stress injury has been presented. We also present the state-of-the-art where transgenic approach has been used to improve stress tolerance in model and crop species by engineering one or more than one of these components of the ROS scavenging machinery.